The Correlation between Stress, Physical Activity and The Menstrual Cycle in Students of Public Health Faculty - Ismi Ismi; Indriati Andolita Tedju Hinga; Sarci Magdalena Toy (Universitas Nusa Cendana, 2020)
Several factors can affect the menstrual cycle, including stress levels and physical activity. An abnormal menstrual cycle will cause several disorders or diseases such as uterine myoma, ovarian endometriosis cysts, uterine adenomyosis. This study aims to determine the relationship between stress levels and physical activity with the menstrual cycle in The Faculty of Public Health Undana Kupang students. This type of research is quantitative with a cross-sectional study design. The population of this study was 541 people and a sample of 86 people, the determination of the sample size used a stratified random sampling formula. Data analysis used the chi-square test with α = 0.05 and a confidence level of 95%. The analysis showed that there was a correlation between stress levels, physical activity, and the menstrual cycle among Faculty of Public Health Undana Kupang students. Stress management by applying good time management, a healthy lifestyle, and regular physical activity are important recommendations to be applied in everyday life.